2021
DOI: 10.3390/jcm10112360
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Contradictory Functions of Lysine Decarboxylase and Butyrate in Periodontal and Intestinal Diseases

Abstract: Periodontal disease is a common, bacterially mediated health problem worldwide. Mastication (chewing) repeatedly traumatizes the gingiva and periodontium, causing traces of inflammatory exudate, gingival crevicular fluid (GCF), to appear in crevices between the teeth and gingiva. Inadequate tooth cleaning causes a dentally adherent microbial biofilm composed of commensal salivary bacteria to appear around these crevices where many bacteria grow better on GCF than in saliva. We reported that lysine decarboxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 178 publications
(269 reference statements)
1
9
0
Order By: Relevance
“…The N1, N8-diacetyl spermidine, and N-acetyl cadaverine levels showed highly signi cant increase in periodontitis with smoker and reverse smoker groups which was similar to previously reported (Goldberg et al, 1994). Elevated levels of lysine in the present study correlated with the study that showed conversion of lysine to cadaverine promotes gingivitis, and lysine depletion promotes gingivitis and periodontitis (Levine & Lohinai, 2021). The failure of GCF exudation in smokers results in the junctional epithelial attachment becoming deprived of amino acids including lysine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The N1, N8-diacetyl spermidine, and N-acetyl cadaverine levels showed highly signi cant increase in periodontitis with smoker and reverse smoker groups which was similar to previously reported (Goldberg et al, 1994). Elevated levels of lysine in the present study correlated with the study that showed conversion of lysine to cadaverine promotes gingivitis, and lysine depletion promotes gingivitis and periodontitis (Levine & Lohinai, 2021). The failure of GCF exudation in smokers results in the junctional epithelial attachment becoming deprived of amino acids including lysine.…”
Section: Discussionsupporting
confidence: 91%
“…The failure of GCF exudation in smokers results in the junctional epithelial attachment becoming deprived of amino acids including lysine. The increase in N acetylcadaverine is tightly associated as putative component of oral malodor and butyrate producing microbiome which lead to enhanced GCF substrate and slowly destroy the periodontium (Goldberg et al, 1994;Levine & Lohinai, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota produces butyrate from acetyl-CoA, lysine, glutarate, or succinate pathways in the colon [ 21 ]. Various bacterial species in the human intestine generate enzymes that can synthesize butyrate from complex fermentable substrates.…”
Section: Butyrate Production Absorption and Metabolismmentioning
confidence: 99%
“…Butyrate, a four-carbon SCFA, is one of the major energy sources for intestinal epithelial cells. Gut microbiota produces butyrate from acetyl-CoA, lysine, glutarate, or succinate pathways in the colon [20]. Various bacterial species in the human intestine generate enzymes that can synthesize butyrate from complex fermentable substrates.…”
Section: Butyrate Production Absorption and Metabolismmentioning
confidence: 99%